1985
DOI: 10.1584/jpestics.10.629
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of the Pyrethroid Insecticide Cypermethrin in Water and on Soil Surface

Abstract: Photodegradation of (1R, cis, ceRS)-and (1R, traps, ceRS)-isomers of Cypermethrin [(RS)-a-cyano-3-phenoxybenzyl(1RS)-cis, traps-3-(2, 2-dichlorovinyl)-2, 2-dimethylcyclopropanecarboxylate] in water and on soil surface was studied, using 14C preparations labeled separately at the cyclopropyl C-1, cyano or benzyl ring. The cis-isomer was photodecomposed 1. 4-1. 7 times faster in sunlight than the traps-isomer in water. The half-life of the cis-isomer was 2. 3-2. 6 days in distilled water and 1 ppm humic acid aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 7 publications
4
18
0
2
Order By: Relevance
“…Mean indirect photolysis depths were reported to be greater than 0.7 mm for outdoor experiments. Several studies (Takahashi et al, 1985; Lartiges and Carrigues, 1995; Zepp et al, 1985; Zafiriou et al, 1984; Jensen‐Korte et al, 1987; Vaughan and Blough, 1998) have indicated that humic acids are capable of acting as sensitizers for the production of reactive intermediates such as singlet oxygen ( 1 O 2 ), hydroxyl radicals (·OH), superoxide anion (·O 2 − ), hydrogen peroxide (H 2 O 2 ), and peroxy radicals (ROO·). For example, sediment‐sorbed DDE photolyzes faster than when it is dissolved, and the product mixture differs in a way that suggests an environment rich in H‐donors, probably organic matter (Zafiriou et al, 1984; Miller and Zepp, 1979).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean indirect photolysis depths were reported to be greater than 0.7 mm for outdoor experiments. Several studies (Takahashi et al, 1985; Lartiges and Carrigues, 1995; Zepp et al, 1985; Zafiriou et al, 1984; Jensen‐Korte et al, 1987; Vaughan and Blough, 1998) have indicated that humic acids are capable of acting as sensitizers for the production of reactive intermediates such as singlet oxygen ( 1 O 2 ), hydroxyl radicals (·OH), superoxide anion (·O 2 − ), hydrogen peroxide (H 2 O 2 ), and peroxy radicals (ROO·). For example, sediment‐sorbed DDE photolyzes faster than when it is dissolved, and the product mixture differs in a way that suggests an environment rich in H‐donors, probably organic matter (Zafiriou et al, 1984; Miller and Zepp, 1979).…”
Section: Resultsmentioning
confidence: 99%
“…There is relatively little information in the open literature on the phototransformation of pesticides under natural environmental conditions (Takahashi et al, 1985; Kochany and Maguire, 1994; Lartiges and Carrigues, 1995; Hebert and Miller, 1990). The present work tries to approximate appropriate environmental conditions using natural sunlight and natural water and soil samples.…”
mentioning
confidence: 99%
“…38) The photoproduct distribution is also similar between cis and trans isomers through the photolysis of permethrin 37) and cypermethrin 38) in water and that of resmethrin on a silica gel surface. 34) Therefore, the experimental results for trans-1 can be reasonably translated to 1.…”
Section: )mentioning
confidence: 88%
“…Although the clear demonstration of photo-induced racemization or enantiomerization by using individual stereoisomer(s) is limited, not only (1R)/(1S) but also trans/cis isomerization was found to proceed in aqueous photolysis of (1R)-trans-and (1R)-cis-isomers of cypermethrin (14). 51) More rapid isomerization of cis-isomers over trans-isomers was observed in water, but the isomerization on soil surfaces was of minor importance. In addition to the (αS) (αR) epimerization at the α-cyanobenzyl carbon, the photo-induced isomerization of deltamethrin (15) proceeded in the cyclopropyl moiety, producing the (1S)-and trans-isomers with the predominance of the (1S)-cis-(αS)-isomer.…”
Section: Radical Reactions and Photolysismentioning
confidence: 99%